The colonizer abroad : American writers on foreign soil, 1846-1912 - McBride, Christopher Mark, 1968- (Literary criticism and cultural theory., 2004)
This book applies postcolonial theory to the travel writing of some of America's best-known authors, revealing the ways in which America's travel fiction and nonfiction have both reflected and shaped society.